In situ TiC particle reinforced TiCuZrNi brazing alloy for joining C/C composites to Ti6Al4V. Issue 3 (23rd January 2018) - Song, Xinrui; Li, Hejun; Casalegno, Valentina; Salvo, Milena; Ferraris, Monica; Zeng, Xierong
Abstract: Chromium carbide modified C/C and Ti6Al4V were successfully joined using a TiCuZrNi brazing alloy in powder form. The braze/composite interface and the mechanical strength of C/C‐Ti6Al4V joints were evaluated. The apparent shear strength of chromium carbide modified C/C joined to Ti6Al4V, measured by single lap test in compression, was 52 ± 6 MPa, which was highest among that without chromium carbide modification (15 ± 2 MPa) and the intrinsic C/C shear strength. The fractography of joints without chromium carbide modification indicated that failure mainly occurred at the TiC layer formed at the composite/braze interface while the joints with chromium carbide modification failed within the C/C.